Incidence, survival, and risk of cardiovascular events in adult inflammatory myopathies in South Korea: a nationwide population-based study. (3rd July 2020) - Jung, KH; Kim, HJ; Park, W; Lim, MJ; Kang, T; Kang, MJ; Kim, K-B; Ahn, HS
Abstract : Objective: Epidemiological studies on inflammatory myopathies (IMs) show widely variable results, and studies on Asians are lacking. Despite emerging interest in the cardiovascular disease (CVD) risk associated with IMs, the prevalence of CVD in IM patients and its impact on mortality remain unclear. We conducted a nationwide, population-based study on the incidence, mortality, and associated major CVD events of IMs in the Republic of Korea over 11 years. Method: Using the nationwide, population-based National Health Insurance claims database and the Rare Intractable Disease registration programme, we estimated incidence, mortality, and CVD occurrence. Survival was examined using the Kaplan–Meier method. Mortality rate in IMs with CVD was analysed by Cox proportional hazards regression. Results: There were 3014 incident cases, 640 of whom died during the study period. The mean annual incidence was 7.16/10 6 . Dermatomyositis (DM) and polymyositis (PM) had 5 year survival rates of 76.8% and 79.3%, respectively. Cardiovascular events occurred in 155 patients and 40.6% of IM patients with CVD died. Acute myocardial infarction in men had the highest risk of any CVD event in both DM [standardized incidence ratio (SIR) 4.2, 95% confidence interval (95% CI) 2.4–7.2] and PM (SIR 3.5, 95% CI 1.8–7.0). Haemorrhagic stroke had the highest hazard ratio (HR) in both DM (HR 2.31, 95% CI 1.13–4.70) and PM patients (HR 2.10, 95% CI 1.03–4.27) compared with the general population with CVD. Conclusion: We found persistently low incidence, poor survival, and high major CVD incidence in IMs, and increased mortality in IMs with CVD.